MANAJEMEN MUTU PEMBELAJARAN AL-QURAN DI SMA ISLAM AL-AZHAR BSD - Irfan Qowwiyul Aziz Alhajj; EE. Junaedi Sastradiharja; Susanto (Jurnal Statement : Media Informasi Sosial dan Pendidikan, 2022)
This research aims to identify and describe the meaning of quality management of Al-Quran learning in Al-Azhar Islamic High School Bumi Serpong Damai (BSD) and identify how the steps for quality management of Al-Quran learning at Al-Azhar Islamic High School BSD are. The results of this research are that what is meant by quality management of al-Quran learning at Al-Azhar Islamic High School BSD is the management of al-Quran learning that is oriented towards quality, which means all of learning aspects starting from planning, implementing, evaluating and learning supervision is entirely carried out on a quality-based basis, including the quality of inputs, quality of processes, and quality of outputs. Al-Azhar Islamic High School BSD has taken four steps to manage the quality of learning: learning planning, learning implementation, learning evaluation, and learning supervision. In the management aspect of Al-Quran learning planning at Al-Azhar Islamic High School BSD, it has been going well although it is still not optimal, this is because the RPP that has been prepared by the teacher still does not meet the RPP standards in the 2013 curriculum. Meanwhile, in the management of implementation’s aspect has been going well and in accordance with the 2013 curriculum standards. Likewise in the aspect of learning evaluation which carries out an evaluation of 3 aspects of learning assessment: attitudes, knowledge and skills, and in the aspect of learning supervision’s management has also been going well and has clear and measurable supervision instruments and makes supervision as a way to improve the professionalism of Al-Quran teachers at Al-Azhar Islamic High School BSD